Monocyte-cancer cell fusion is mediated by phosphatidylserine—CD36 receptor interaction and induced by ionizing radiation - Ivan Shabo; Kristine Midtbö; Robert Bränström; Annelie Lindström (PLoS ONE, 2025)
Emerging evidence suggests that fusion of cancer cells with leucocytes, such as macrophages, plays a significant role in cancer metastasis and results in tumor hybrid cells that acquire resistance to chemo- and radiation therapy. However, the precise mechanisms behind the leukocyte-cancer cell fusion remain unclear. The present in vitro study explores the presence of fusion between the monocyte cell line (THP-1) and the breast cancer cell line (MCF-7) in relation to the expression of CD36 and phosphatidylserine with and without treatment of these cells with ionizing radiation. The study reveals that spontaneous THP-1/MCF-7 cell fusion increases significantly from 2.8% to 6% after irradiation. The interaction between CD36 and phosphatidylserine plays a pivotal role in THP-1/MCF-7 cell fusion, as inhibiting this interaction using anti-CD36 antibodies significantly reduces cell fusion. While irradiation leads to a dose-dependent escalation in phosphatidylserine expression in MCF-7 cells, it does not impact the expression of CD36 in either THP-1 or MCF-7 cells. To the best of our knowledge, this is the first study to demonstrate the involvement of the CD36-phosphatidylserine interaction in the fusion between monocytes and cancer cells, shedding light on a novel explanatory mechanism for the roles of CD36 and phosphatidylserine in tumor progression.